MOOCs for Professional Development of Teachers through E-Learning System: The Indian Scenario - Kayal, Soumen; Kayal, Baisakhi Das (Journal of Information and Knowledge, 2020)
E-learning is an innovative approach to utilize Information and Communication Technology (ICT) to provide learning opportunities to a wide audience. It allows interaction between learners and teachers. In recent years, in order to adapt to the changing role of the teachers to accommodate 21st century learning practices, E-learning has changed teaching-learning in the higher education system of India. The Annual Refresher Programme in Teaching (ARPIT) is one of the gateways of E-learning system for in-service teachers of college and university in India. Academic libraries also play vital role in the changing method of teaching and learning process for MOOCs development. The purpose of this paper is to present changes in the use of the technology in online learning and universal access to knowledge through Swayam, the platform for offering Massive Open Online Courses (MOOCs) in India. The findings revealed that the online refresher course has different parameters or factors which provide information about distinct aspects of MOOCs for professional development and engagement of in-service teachers